Mathematics (T) term 1 - Lee, Yoon Woh; Tan Guan Hin; Tey Kim Soon (Pre-U STPM Text, 2018)
This book is specially designed for students who are sitting for the STPM examination. The comprehensive notes and practices are based on the latest syllabus and exam format set by Majlis Peperiksaan Malaysia. This book will provide you with the necessary skills and strategies to excel in the subject.